Stigma Sosial dan Kesejahteraan Psikologis: Studi Fenomenologi Mengenai Pengalaman Hidup Anak Pendeta: Penelitian - Nova Lisye Sinaulan; Marssel Michael Sengkey; Imanuel Erens Sumenge; Afillio Fordy Akhail Dinar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to deeply explore the life experiences of pastor's children in Tataaran I Village related to the social stigma they face and how they interpret its impact on their psychological well-being. Using a qualitative approach with a phenomenological design, this study delves into the subjective perspectives of six participants through in-depth interviews. The thematic analysis results reveal three main themes: (1) Living in a 'Glass House': Constant Surveillance and Expectations; (2) Navigating Dual Identities: Between 'Ordinary Child' and 'Pastor's Child'; and (3) Stigma as a Burden and Catalyst for Growth. The findings indicate that social stigma creates a significant psychological burden, particularly in aspects of self-acceptance and autonomy. However, these challenges can also become drivers of resilience and personal growth when successfully negotiated.